Hubungan Anemia pada Ibu Hamil dengan Kejadian Atonia Uteri di Rs Charis Medika Kota Batam - Kasih Purwati; Acholder Sirait; Anindya Novita (Universitas Batam, 2022)
Background: Anemia in pregnancy can cause uterine atony. Uterine atony is a failure of uterine myometrial muscle fibers to contract, uterine atony that is not handled properly can result in shock and can decrease consciousness and result in maternal death Method:This study method is observational analytic with cross sectional approach which was conducted at Charis Medika Hospital, Batam city. Data was taken using Medical Record data. The sampling technique in this study used total sampling with a total sample of 2,627 respondents. The results of the study were presented in the form of a frequency distribution and were cross tabulated and then tested with Fisher to determine the existence of a relationship. Results: The characteristics of patients with anemia and uterine atony as were 7 people (0.3%) patients with anemia but no atony were 58 people (2.2%) patients who were not anemia but had atony were 22 people (0.8% ) and patients who are not anemia and do not experience uterine atony weres 2,540 people (96.7%). Fisher's analysis obtained p = 0.000 (<0.05). Ho is rejected, which means that there is a relationship between anemia in pregnancy and the incidence of uterine atony at Charis Medika Hospital. Conclusion: There was a significant relationship between anemia in pregnancy and the incidence of uterine atony at Charis Medika Hospital, Batam city in 2020-2021